2018
DOI: 10.36108/nje/8102/43(0180)
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Insecticide Susceptibility Status of Anopheles gambiae Complex (Giles, 1902) in Osun State, Southwestern Nigeria

Abstract: A major challenge facing malaria control today is the high spate of insecticide resistance in mosquito populations. The present study was designed to investigate the susceptibility of An. gambiaes.l. to Dichlorodiphenyltrichloroethane (DDT) and Deltamethrin, and determine the sibling species at selected locations in Osun State, Nigeria. Larvae of An. gambiae complex were collected from Ibokun, Ife, Ede, Osogbo, Okuku and Iwo representing the three geopolitical zones in Osun State. Two to three day old unfed fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
2
3
0
Order By: Relevance
“…According to the WHO (1996), Culex, Aedes and Anopheles species have developed resistance rapidly to various insecticides in many countries, but Culex can develop resistance more rapidly to insecticides than other mosquitoes. The high resistance of A. gambiae s. l. , C. quinquefasciatus and A. aegypti compared with OC-control and DDT (p=0.0004; p<0.05), is in conformity with previous studies where emerging resistance to DDT have been reported (Adeleke et al , 2018). Resistance was high but moderate in Permethrin (48%) and Deltamethrin (60%) (p=0.002; p<0.05).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…According to the WHO (1996), Culex, Aedes and Anopheles species have developed resistance rapidly to various insecticides in many countries, but Culex can develop resistance more rapidly to insecticides than other mosquitoes. The high resistance of A. gambiae s. l. , C. quinquefasciatus and A. aegypti compared with OC-control and DDT (p=0.0004; p<0.05), is in conformity with previous studies where emerging resistance to DDT have been reported (Adeleke et al , 2018). Resistance was high but moderate in Permethrin (48%) and Deltamethrin (60%) (p=0.002; p<0.05).…”
Section: Discussionsupporting
confidence: 92%
“…This could be due to reported cases of vector resistance to organochlorine class of insecticides (Adeogun et al, 2022). According to the WHO (1996), where emerging resistance to DDT have been reported (Adeleke et al, 2018). Resistance was high but moderate in Permethrin (48%) and Deltamethrin (60%) (p=0.002; p<0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…quinquefasciatus and A . aegypti compared with OC-control and DDT (p = 0.0004; p<0.05), is in conformity with previous studies where emerging resistance to DDT have been reported [ 9 ]. Resistance was high but moderate in Permethrin (48%) and Deltamethrin (60%) (p = 0.002; p<0.05).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the distribution of larval habitats and insecticide susceptibility status of A . gambiae complex is yet unknown in the State [ 9 ]. Thus, the need for the present study in assessing whether mosquitoes in Osogbo metropolis are resistant or susceptible to insecticides currently used for vector control of adult mosquitoes with a view to corroborating global efforts in the prevention and eradication of mosquito-borne diseases.…”
Section: Introductionmentioning
confidence: 99%